1997
DOI: 10.1590/s0102-76381997000200012
|View full text |Cite
|
Sign up to set email alerts
|

Pericárdio bovino utilizado como remendo no sistema cardiovascular

Abstract: O comportamento do pericárdio bovino, preservado em glutaraldeído, na confecção de próteses valvulares é bem conhecido. Embora amplamente empregado na forma de retalho, foi pouco estudado neste sentido. Com esta finalidade, 21 cães foram submetidos ao implante cirúrgico de um retalho padronizado de pericárdio bovino substituindo, parcialmente, as paredes da aorta, do átrio esquerdo e do pericárdio. Os cães foram, casualmente, separados em três grupos, segundo o tempo de reoperação. O Grupo 1 com 6 cães reopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
1
2
0
1
Order By: Relevance
“…We observed, in both groups, that the calcification was more intense in the valvular cusps than on the conduit walls, confirming the observations of Gabbay et al [7] and Pires et al [6] that calcification depends not only on the implantation site, but also on the mechanical stress over the tissue. This was also evident in the radiographic analysis, where we could observe, in the GDA group, more intense concentrations of calcium in the commissural regions and the in leaflet base along to its insertion into the conduit, with patterns similar to those described by Flameng et al [22] in bovine pericardial bioprosthesis implanted in mitral position of sheep.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed, in both groups, that the calcification was more intense in the valvular cusps than on the conduit walls, confirming the observations of Gabbay et al [7] and Pires et al [6] that calcification depends not only on the implantation site, but also on the mechanical stress over the tissue. This was also evident in the radiographic analysis, where we could observe, in the GDA group, more intense concentrations of calcium in the commissural regions and the in leaflet base along to its insertion into the conduit, with patterns similar to those described by Flameng et al [22] in bovine pericardial bioprosthesis implanted in mitral position of sheep.…”
Section: Discussionsupporting
confidence: 92%
“…However, progressive tissue degeneration, especially due to the occurrence of dystrophic calcification, still represents a major limitation for the clinical use of biological valve prostheses. The mechanisms responsible for calcification are multifactorial [6][7][8][9], however, it is known that one major cause is due to electrostatic attraction among circulating calcium, phospholipids present in membranes and cellular debris from fixed tissues [10,11]. In addition, the release of residual aldehyde is cytotoxic, causing inflammatory reactions and working as an initial site of calcium deposition [11].…”
Section: Introductionmentioning
confidence: 99%
“…In 1997, Pires et al [77] demonstrated that bovine pericardial tissue implanted in the atrium calcifies, retracts and promotes thrombus formation. The variation proposed by Van De Wal et al, without the use of prosthetic material, using the retail from the own right atrial wall by confection of the tunnel [72], aimed to improve the outcome in the short term, because it keeps the tunnel contraction, allowing improved systemic venous drainage.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…O pericárdio bovino é uma das fontes que há três décadas vem sendo utilizado na confecção de biomateriais 1,2,4,6,7,14,17,27 . Entretanto, até o momento, poucas informações estão disponíveis quanto ao seu potencial como carreador de células na engenharia de tecidos.…”
Section: Introductionunclassified